2014
DOI: 10.1088/1674-1056/23/3/034203
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement of two two-level atoms trapped in coupled cavities with a Kerr medium

Abstract: In this paper, the entanglement dynamics of two two-level atoms trapped in coupled cavities with a Kerr medium is investigated. We find that the phenomena of entanglement sudden death (ESD) and entanglement sudden birth (ESB) appear during the evolution process. The influences of initial atomic states, Kerr medium, and cavity-cavity hopping rate on the atom-atom entanglement are discussed. The results obtained by the numerical method show that the atomatom entanglement is strengthened and even prevented from E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…So far, there has been much literature on the dynamics of a bipartite atomic system under different kinds of environments including independent and common ones. [5][6][7][8][9] It is observed that in the non-Markovian reservoirs, the entanglement sudden birth appearing after complete disappearance depends on the initial state of the system. [10,11] Besides, in the thermal and vacuum environments, taking into account the two atoms close together, due to the presence of collective damping and dipole-dipole interaction, Tahira et al [12][13][14][15][16] found the revival of entanglement and the oscillatory behavior.…”
Section: Introductionmentioning
confidence: 99%
“…So far, there has been much literature on the dynamics of a bipartite atomic system under different kinds of environments including independent and common ones. [5][6][7][8][9] It is observed that in the non-Markovian reservoirs, the entanglement sudden birth appearing after complete disappearance depends on the initial state of the system. [10,11] Besides, in the thermal and vacuum environments, taking into account the two atoms close together, due to the presence of collective damping and dipole-dipole interaction, Tahira et al [12][13][14][15][16] found the revival of entanglement and the oscillatory behavior.…”
Section: Introductionmentioning
confidence: 99%